2021
DOI: 10.1111/nph.17431
|View full text |Cite
|
Sign up to set email alerts
|

The MdMYB16/MdMYB1‐miR7125‐MdCCR module regulates the homeostasis between anthocyanin and lignin biosynthesis during light induction in apple

Abstract: Light induces anthocyanin accumulation and hence decides the coloration of apple fruit. It also plays a key role in regulating the biosynthesis of other secondary metabolites. However, the crosstalk between anthocyanin and lignin metabolism during light induction, which affects the edible quality and visual quality of apple fruit, respectively, have rarely been characterized.In this study, we identified and functionally elucidated the roles of miR7125 and its target, cinnamoyl-coenzyme A reductase gene (CCR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 66 publications
2
38
0
Order By: Relevance
“…Both our expression pro les and a previous study on MaMYB54 (TT2L3) and MaMYB39 (MYB4) support this postulation [24]. The homeostasis between anthocyanin and lignin biosynthesis regulated by MYBs was also reported in apples [30].…”
Section: Discussionsupporting
confidence: 88%
“…Both our expression pro les and a previous study on MaMYB54 (TT2L3) and MaMYB39 (MYB4) support this postulation [24]. The homeostasis between anthocyanin and lignin biosynthesis regulated by MYBs was also reported in apples [30].…”
Section: Discussionsupporting
confidence: 88%
“…As transgenic apple plants exhibit a prolonged juvenile stage, the present work conducted transient transfection for silencing MdMYB306‐like in juvenile ‘Yinv’ fruit and for overexpressing MdMYB306‐like in coloring ‘Yinv’ fruit, mediated by Agrobacterium infection. This approach has been extensively applied to investigate the roles of genes in apple fruit (Hu et al., 2021; Ma et al., 2021; Yang et al., 2021). Compared with the control, the transient silencing of MdMYB306‐like significantly induced anthocyanin accumulation near the injection site; conversely, the overexpression of MdMYB306‐like inhibited anthocyanin accumulation near the injection site (Figure 3a–c), which suggested that MdMYB306‐like plays an inhibitory role in anthocyanin synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Both our expression profiles and a previous study on MaMYB 54 ( TT2L3 ) and MaMYB39 ( MYB4 ) support this postulation [ 24 ]. The homeostasis between anthocyanin and lignin biosynthesis regulated by cooperation of repressor MdMYB16 and activator MdMYB1 was also reported in apples [ 92 ].…”
Section: Discussionmentioning
confidence: 91%